Ad fontes! L’uso di strumenti retorici classici nei discorsi politici attuali: l’esempio dei negoziati di coalizione in Germania (2017-2018) (PHRASIS | Rivista di studi fraseologici e paremiologici, 2019)
This article deals with the use of rhetorical structures in current political discourses. The humanistic motto Ad fontes! refers to the assumption that even today politicians still use the classical means of rhetoric in their public speeches in order to present their positioning as clearly, attractively and convincingly as possible with appropriate linguistic statements. But with what subtleties do politicians construct their statements so that they persuade the audience? For this reason, the focus lays on a rhetorical analysis of public statements by politicians of the most important German parties in the 2017 Bundestag elections, in relation to the negotiations to form a coalition government in the period 2017-2018.
Keywords: Political Language; Rhetorical Political Analysis; German Politicians and Rhetoric; Rhetorical and Phraseological Structures in Political Discourse